Five-year atmospheric corrosion of Cu, Cr and Ni weathering steels in a wide range of environments. (15th August 2018) - Díaz, I.; Cano, H.; Lopesino, P.; de la Fuente, D.; Chico, B.; Jiménez, J.A.; Medina, S.F.; Morcillo, M.
Highlights: Addition of Ni (3.0 wt%) promotes a notable increase in corrosion resistance. To unpainted use: In ISO C2 atmospheres: all the tested steels. In ISO C3 atmospheres: the steels alloyed with 0.50 wt% Cr or 3.0 wt% Ni. In ISO > C3 atmospheres: none of the tested steels. Abstract: This work considers fourteen weathering steels manufactured by adding Cu, Cr and Ni alloying elements to extra mild steel. The steels were exposed for up to 5 years in different atmospheres. The atmospheric corrosion resistance of the steels was evaluated and the rust layers formed were characterised by X-ray diffraction, optical microscopy and scanning electron microscopy. The addition of Ni, particularly at 3.0 wt%, leads to a notable increase in corrosion resistance. The rusts formed contain lepidocrocite, goethite and spinel phases. X-ray diffraction also detected small amounts of kornelite (industrial atmosphere) and akaganeite (marine atmosphere).